Розроблення інформаційної системи для покращення ментального здоров'я у воєнний та післявоєнний періоди - Костерева, Софія Романівна; Kostereva, Sofiia Romanivna (Національний університет "Львівська політехніка", 2024)
Проблема ментального здоров’я в Україні, загострена тривалим збройним конфліктом, є однією з ключових соціальних та гуманітарних проблем сучасності. Війна спричинила значне зростання психологічних розладів, зокрема тривожності, депресії та посттравматичного стресового розладу (ПТСР). Актуальність теми зумовлена необхідністю створення доступних, технологічно підтримуваних рішень для забезпечення психологічної підтримки, самодопомоги та соціальної реінтеграції в умовах воєнного та післявоєнного періодів. У даній роботі проаналізовано вплив війни на психоемоційний стан населення та потреби цільової аудиторії, що включають безпечний простір для емоційної підтримки, доступ до професійної психотерапії, освітні матеріали та можливості для соціальної взаємодії. Оцінено існуючі цифрові платформи, виявлено їхні сильні сторони та обмеження. На основі цього сформульовано технічні, функціональні та нефункціональні вимоги до інформаційної системи. Реалізовано серверну частину для обробки запитів та управління даними, а також клієнтську частину для створення інтуїтивного, адаптивного інтерфейсу. Проведено тестування, результати якого також показали відповідність системи вимогам доступності та стабільності. Об’єктом дослідження є інформаційна система для підтримки ментального здоров’я українців у воєнний та післявоєнний періоди. Предметом дослідження є розроблення, налагодження та практична реалізація платформи для забезпечення психологічної підтримки, самодопомоги та соціальної взаємодії. Мета роботи полягає у створенні інформаційної системи, яка забезпечує швидкий і зручний доступ до психологічних консультацій, освітніх ресурсів та соціальних ініціатив для підтримки ментального здоров’я населення, постраждалого від війни. Новизна інформаційної системи полягає у створенні комплексного підходу до підтримки ментального здоров’я, який поєднує адаптивний інтерфейс та орієнтацію на вразливі групи населення. Система пропонує унікальне поєднання довгострокової психологічної підтримки та доступу до освітніх матеріалів, що сприяє підвищенню психологічної стійкості та соціальної реінтеграції. На відміну від конкурентів, вирізняється розвиненою соціальною взаємодією, реалізованою через інтеграцію вебінарів і групових онлайн-заходів, які створюють спільноту для обміну досвідом і подолання ізоляції. Практичне значення результатів дослідження полягає у розробці якісного інструменту для психологічної підтримки, який може бути використаний як індивідуальними користувачами, так і організаціями для надання допомоги в кризових умовах. Система забезпечує швидкий доступ до фахівців, ресурсів самодопомоги та інформації про соціальні заходи, що сприяє зменшенню психологічного навантаження та підвищенню якості життя. Ключові слова: ментальне самодопомога, соціалізація. Перелік використаних джерел: 1. здоров’я, психологічна підтримка, Amsalem D., Haim-Nachum S., Lazarov A., Levi-Belz Y., Markowitz J. C., Bergman M., Klein Rafaeli A., Brenner L. A., Nacasch N., Wainberg M. L., Lurie I., Mendlovic S. & Neria Y. (2025). The effects of war-related experiences on mental health symptoms of individuals living in conflict zones: A longitudinal study. Scientific Reports, 15(1), 889. https://doi.org/10.1038/s41598-024-84410-3 2. Osokina О., Silwal S., Bohdanova T., Hodes, M., Skokauskas N. & Sourander, A. (2023). Impact of the Russian invasion on mental health of adolescents in Ukraine. Journal of the American Academy of Child & Adolescent Psychiatry, 62(3), 335–343. https://doi.org/10.1016/j.jaac.2022.07.845

The issue of mental health in Ukraine, intensified by the prolonged armed conflict, represents one of the most pressing social and humanitarian challenges of our time. The war has led to a significant increase in psychological disorders, including anxiety, depression, and post-traumatic stress disorder (PTSD). The relevance of this topic stems from the urgent need to develop accessible, technology-supported solutions to provide psychological support, self-help resources, and social reintegration during and after the wartime period. This study analyzes the impact of the war on the psycho-emotional state of the population and the needs of the target audience, which include a safe space for emotional support, access to professional psychotherapy, educational materials, and opportunities for social interaction. Existing digital platforms were evaluated, identifying their strengths and limitations. Based on this analysis, technical, functional, and non-functional requirements were formulated for the development of an information system. The server-side component was implemented to handle requests and manage data, while the client-side component was designed to create an intuitive, adaptive interface. Testing confirmed the system meets accessibility and stability requirements. Object of the study is the information system designed to support the mental health of Ukrainians during and post-war periods. Subject of the study is the development, configuration, and practical implementation of a web application to provide psychological support, self-help, and social interaction. The purpose of this work is the creation an information system that ensures rapid and convenient access to psychological consultations, educational resources, and social initiatives to support the mental health of the war-affected population. The novelty of the information system lies in its comprehensive approach to mental health support, combining an adaptive interface and a focus on vulnerable population groups. The system offers a unique blend of long-term psychological support and access to educational materials, fostering psychological resilience and social reintegration. Unlike competitors, it stands out with enhanced social interaction through the integration of webinars and group online events, creating a community for experience sharing and overcoming isolation. The practical significance of the study lie in the development of an effective tool for psychological support, which can be utilized by both individual users and organizations to provide assistance in crisis conditions. The system ensures quick access to specialists, self-help resources, and information about social initiatives, contributing to the reduction of psychological stress and improvement of quality of life.
Development of an information system to improve mental health during and after wartime
Keywords: 6.122.00.00; mental health; psychological support; self-help; socialization. List of used sources: 1. Amsalem D.; Haim-Nachum S.; Lazarov A.; Levi-Belz Y.; Markowitz J. C.; Bergman M.; Klein Rafaeli A.; Brenner L. A.; Nacasch N.; Wainberg M. L.; Lurie I.; Mendlovic S. & Neria Y. (2025). The effects of war-related experiences on mental health symptoms of individuals living in conflict zones: A longitudinal study. Scientific Reports; 15(1); 889. https://doi.org/10.1038/s41598-024-84410-3 2. Osokina О.; Silwal S.; Bohdanova T.; Hodes; M.; Skokauskas N. & Sourander; A. (2023). Impact of the Russian invasion on mental health of adolescents in Ukraine. Journal of the American Academy of Child & Adolescent Psychiatry; 62(3); 335–343. https://doi.org/10.1016/j.jaac.2022.07.845 3. Euronews. (2023). War in Ukraine having a devastating impact on people's mental health. Access Mode: https://www.euronews.com/2023/02/20/war-in ukraine-having-a-devastating-impact-on-peoples-mental-health